Peningkatan Kapabilitas Pengelola Keuangan Badan Layanan Umum Daerah Dalam Rangka Pencegahan Fraud di Kabupaten Pinrang - Indrijawati, Aini; Darmawati, Darmawati; Kartini, Kartini; Syamsuddin, Syamsuddin; Rasyid, Syarifuddin; Purisamya, Asharin Juwita; Juanda, Indira Syakira Kirana (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Regional Public Service Agencies (BLUD) play a strategic role in supporting public services, particularly in the health sector. However, financial management in BLUD often faces challenges such as fraud risks and weak internal control systems. This Community Service Program aims to enhance the financial management capacity of BLUD managers in Pinrang Regency to prevent fraud. The methods employed include intensive training, case study simulations, technical assistance, and evaluation of the implementation of internal control systems. The results show improved participants' understanding of fraud concepts and the application of more effective prevention measures. Technical assistance enabled BLUD managers to design and implement internal control systems tailored to the needs of each unit. This program successfully fostered more transparent and accountable financial governance, supporting the sustainability of public services. As a follow-up, it is proposed that similar activities be conducted periodically to ensure the continuous improvement of BLUD managers' capabilities. Additionally, the development of digital platforms is recommended to support more integrated and efficient financial reporting. These steps are expected to strengthen BLUD financial governance in Pinrang Regency and serve as a model for adoption in other regions.